3D‐Assembled Bionic Tactile Sensing “Skin” for Soft Machines - Ruiping Zhang; Yihao Chen; Ziheng Wang; Ziwei Liang; Yinji Ma; Ying Chen; Xue Feng (Advanced Sensor Research)
Abstract Soft machines such as bionic soft robotics attract tremendous interest. Environmental awareness between the “skin” of robotics and the contact surface is essential for motion control. Contact sensing requires not only bionic tactile perception but also high adaptability to their skin's soft nature. However, most tactile sensors can only measure normal pressure and are not adapted to large‐area soft surfaces. Here, a multi‐directional bionic tactile sensing “skin” (MBT‐Skin) for soft machines is developed. The skin can detect pressure and friction simultaneously with its 3D structure. Through curvature‐controlled transfer printing and multi‐step 3D assembly, multiple 3D structures with a small size (1.4 mm × 1.2 mm × 4 mm) are fabricated efficiently. The sensor possesses high sensitivity (P: −0.013N−1; f: 0.036 N−1), good linearity (P: R2 = 0.990; f: R2 = 0.999), and robust repeatability (≈1000). For MBT‐Skin, stretchable interconnections are designed to adapt to the large skin deformation of soft machines. It is mounted on a soft snake‐like cylinder and detects multi‐direction force mimicking tactile perception during soft robotics movement. The results show that MBT‐Skin is capable of detecting pressure and friction with minimal interference from machine bending, which demonstrates its potential future applications in environmental awareness for bionic soft robotics.